Payments for Environmental Services (PES): a study on brazilian legislation and the structuring of agreements (Research, Society and Development, 2020)
The land use and occupation in Brazil was marked by the decrease of the vegetation coverage and anthropic modifications in the different ecosystems, distributed among Brazilian biomes: Amazonia, Cerrado, Caatinga, Atlantic Forest, Pantanal and Pampas. Nowadays, the approach about the ecosystems conservation and recovery needs have strengthened in national and international levels, developing economic instruments which helps the environmental management. This work aims to discuss the Payments for Ecosystem Services (PES) in the Brazilian context, addressing the legal aspects on the Federal and State scopes in the five geographical regions: Southeast, North, Northeast, Central West and South. Furthermore, introduces the procedure for structuring the agreements that enables the understanding of how this economic instrument may help the restoration and conservation of ecosystems using the Payments for Ecosystem Services, which supports the maintenance of the Ecosystem Services that stems from anthropic activities. The adopted methodology was a bibliographic review of academic articles, manuals, theses and Brazilian legislation about the Payments for Ecosystem Services. The results and discussion showed that even without a Nacional Policy that concerns about the Payments for Ecosystem Services, several states in Brazil developed their own policies about this subject. However, the PES has not been effectively implemented in some regions of the country that have a great potential to develop agreements, as in the case of Northeast.